Quality Analysis Of Cayenne Pepper (Capsicum Frutescens L) Variety Ori 212 With Addition Of Natural Preservative Edible Coating Cassava Peel Starch During Room Temperature Storage - Pangestu, Wahyu Aji; Nur’aini, Vivi; Puyanda, Irvia Resti (Jurnal Teknologi Pangan, 2024)
Cayenne pepper is a horticultural plant whose fruit has a complete combination of color, taste and nutritional value but is not very durable for storage. This research is aimed at determine the effectiveness of edible coating immersion time and storage time on the physical, chemical, microbiological and organoleptic characteristics of ORI 212 variety cayenne pepper. Researched used a completely randomized design with 2 factors; first factor is immersion time in edible coating is 0 sec, 60 sec, 180 sec and second factor is the storage time on days 0, 10, 20. The research began with making edible coating from cassava peel starch with the addition of red ginger extract. Edible coating was applied to the ORI 212 variety of cayenne pepper with an immersion time of 60 sec, 180 sec and stored for 20 days. On days 0, 10, 20, moisture content, weight loss, color, vitamin C, organoleptic and total plate number tests were carried out. The results showed that edible coating cassava peel starch with a immersion time of 60 sec was the most effective treatment which could maintain moisture content on the 20th day of 40.42% and a lower weight loss reduction of 68.24%. From the results the color test, it can maintain brightness 24.85, reddish 37.73, yellowish 22.07 and has the highest score in the organoleptic test. The growth of microbial numbers was lower on day 20 with 5.86 CFU/gram but did not have a significant effect on vitamin C with other treatments. The length of storage has an influence on the effectiveness of edible coating cassava peel starch, the longer the storage, the quality of the cayenne pepper will decrease.Keywords : Edible coating, cayenne pepper, immersion time, storage time